Comprendre l’expérience critique ordinaire : Enjeux épistémiques et méthodologiques d’une enquête sur l’hésitation vaccinale - Jérôme Gaillaguet (Questions Vives, 2022)
This paper addresses epistemic and methodological stakes of a study on vaccine hesitancy, and its relations with public controversies. Our interrogation takes into account a double problem: the dynamic of actors and arguments in controversial processes; and defiance or resistance phenomenon as outcomes of those processes. Indeed, one of the most remarkable aspects of vaccine hesitancy, considered as an attitude, is that it is subject to significant variations throughout time. From that stand point, this paper wonders how to design a survey that allows to analyze attitudes considering their variability throughout time, and the evolving sociocultural contexts in which they take place? First, we discuss the theoretical tools that allow the analysis of controversies. Secondly, we propose a methodological frame through 3 logics of investigation that allow to grasp experience as a process. Finally, we present two results as outcomes of our methodological design: that vaccine hesitancy is not limited to ideological adherence; and that the attitude does not determine the decision making.